Monitoring Unfractionated Heparin in Adult Patients Undergoing Extracorporeal Membrane Oxygenation (ECMO): ACT, APTT, or ANTI-XA? - Tung Phi Nguyen; Xuan Thi Phan; Dai Quang Huynh; Ha Thi Viet Truong; Yen Nguyen Hai Le; Tuan Manh Nguyen; Quan Quoc Minh Du; Thao Phuong Le; Hai Ngoc Truong; Thi Thi Ho; Thao Thi Ngoc Pham (Critical Care Research and Practice)
Background. During ECMO, anticoagulants, in particular, unfractionated heparin (UFH), are commonly used and monitored by laboratory tests, including ACT, APTT, and anti-Xa level. Method. A single-center retrospective observational study was conducted on adult patients undergoing ECMO between January 2019 and January 2020 at a tertiary hospital. The correlations between ACT, APTT, anti-Xa, antithrombin, and UFH dose were assessed. Results. 129 sets of measurements from 37 patients were obtained including ACT, APTT, anti-Xa, antithrombin, and UFH dose measured simultaneously. 102 out of 129 sets of values were interpreted as antithrombin deficiencies. The correlation coefficient between APTT and anti-Xa; ACT and anti-Xa are 0.72 and 0.33, respectively, p<0.001. The patients with normal antithrombin levels exhibited a significant correlation between APTT and anti-Xa (r = 0.80, p<0.001). ACT, on the other hand, was poorly correlated with UFH dose, whether there is AT deficiency or not. Anti-Xa and APTT are only moderately correlated with UFH dose in the group without antithrombin deficiency, with correlation coefficients of 0.62 and 0.57, respectively, p<0.05. Conclusion. APTT value is strongly correlated with anti-Xa value, particularly in patients with normal antithrombin levels. However, the ACT value was poorly correlated with anti-Xa and not with the UFH dose. In groups without antithrombin deficiency, APTT and anti-Xa values only moderately correlated with UFH dose.